Sistemas de cultivo com milho e braquiária e nitrogênio em cobertura no feijoeiro em sucessão no plantio direto - Mingotte, Fábio Luíz Checchio [UNESP] (2015)
The production and the maintenance of the soil cover represent the principal difficult to no-tillage system establishment in regions with warm and humid summer and dry winter, leading to the deepening of the research on the use of grasses like as corn and brachiaria in exclusive cropping and intercropping systems. In these regions, the irrigated common bean in succession to grasses in no-tillage system it is advantageous due to its relatively short cycle and high profitability in the harvest off season. Considering the production system as a whole, the increase on straw mulch production on soil surface can influence in the soil nitrogen dynamics, being necessary the deepening of the research on the economic viability of the application of this nutrient in agricultural production systems and their effects on the agronomic performance of cultivated plants and in the improving the quality of the harvested products. The work was carried out during the 2011/12 and 2012/13 crop years on a Eutrophic Oxisol, in Jaboticabal-SP-Brazil, aiming to evaluate the agronomic performance and production of straw mulch provided by corn and Urochloa ruziziensis cultivated exclusively and intercropping, and to verify the residual effect of the nitrogen topdressed on predecessor common bean. Another objective of this work was to evaluate the effects of predecessor cropping system and the nitrogen topdressed split application in agronomic performance, economical viability and technological attributes of common bean cultivated in succession to corn and U. ruziziensis exclusives and intercropping in no-tillage system. The experimental design was a randomized complete block arranged in a split-plot scheme with four replications. The plots had been represented for three crop systems with corn exclusive, corn and U. ruziziensis intercropping and U. ruziziensis exclusive, all in succession to the irrigated common bean sown in August in no-tillage system. In the ...